Kontestasi Komunikasi Lintas Agama pada Masyarakat di Wilayah Tapanuli Utara dalam Membangun Moderasi Beragama - Hutagalung, Zulkarnain; Sazali, Hasan (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The contestation of interfaith communication in North Tapanuli, Indonesia, reflects the region's long and diverse history of religious interactions. This study aims to explore the factors influencing interfaith communication and to promote religious moderation. A qualitative descriptive method with an ethnographic approach was utilized to identify and analyze the dynamics of interreligious communication. The findings indicate that historical, social, and theological factors play significant roles in shaping current religious interactions, while religious institutions like the FKUB are crucial in facilitating dialogue and cooperation. This research suggests that a more inclusive and dialogical approach to religious communication can strengthen tolerance and harmony in multicultural societies.